An approach toward higher electrical conversion efficiency of solar photovoltaic module using phase change materials. Issue 6 (28th June 2022) - Nandanwar, Yogesh N.; Kalbande, Vednath P.; Mohan, Man; Rambhad, Kishor; Walke, Pramod V.
Abstract: A well‐known fact is that the electrical performance of the solar photovoltaic (PV) module reduces with an increase of its operating surface temperature, hence to obtain better electrical performance from PV module; it becomes necessary to maintain its surface temperature within the recommended limit. The present experimentation is focused on the application of phase change materials (PCM) to improve the electrical conversion efficiency of the PV module. The performance analysis of the polycrystalline silicon PV module integrated with the finned heat sink embedded in the PCM bath has been carried out, particularly for Indian climatic conditions (21°N, 79°E). Four different organic PCM‐filled PV modules (PV‐PCM) have been selected for performance comparison with conventional PV modules toward their electrical conversion efficiency. All the PV modules are tested with different tilt angles to obtain the lowest operating temperature afterwards the PV‐PCM module with the lowest temperature at particular tilt angle was compared with conventional PV module for output power. Among all investigated PV modules, calcium chloride hexahydrate‐filled PV system exhibits the highest electrical performance at an angle of 90° with the horizontal. The relative and improved average electrical efficiency of 7.5% was recorded with the novel designed PV‐PCM system. Abstract :